2002
DOI: 10.1136/bmj.325.7369.864
|View full text |Cite
|
Sign up to set email alerts
|

Oral pristinamycin versus standard penicillin regimen to treat erysipelas in adults: randomised, non-inferiority, open trial

Abstract: Objective To assess the efficacy and safety of oral pristinamycin versus intravenous then oral penicillin to treat erysipelas in patients in hospital. Design Multicentre, parallel group, open labelled, randomised non-inferiority trial. Setting 22 French hospitals. Participants 289 adults admitted to hospital with erysipelas. Results At follow up (day 25-45) the cure rate (primary efficacy end point) for the per protocol populations was 81% (83/102) for pristinamycin and 67% (68/102) for penicillin. The planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Although it may be a potentially severe disease, erysipelas can usually be controlled with oral/parenteral antibiotics [3]. Potential local risk factors described in the medical literature were edema, lymphedema, cutaneous barrier rupture, superficial or deep venous insufficiency, history of leg surgery, radiation therapy (inferior limb or pelvis) and leg neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Although it may be a potentially severe disease, erysipelas can usually be controlled with oral/parenteral antibiotics [3]. Potential local risk factors described in the medical literature were edema, lymphedema, cutaneous barrier rupture, superficial or deep venous insufficiency, history of leg surgery, radiation therapy (inferior limb or pelvis) and leg neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Erysipelas is an acute bacterial dermal-hypodermal infection (cellulitis) that usually affects the legs and is commonly caused by streptococci [1]. Recurrence is considered its most frequent complication (6.7–29%) [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Both drugs have a high level of antistreptococcal activity. The cure rates (per protocol and intention to treat) were 81% and 65% for pristinamycin in comparison with 67% and 53% for penicillin, both statistically significant differences (per-protocol absolute risk difference, 14%; 97.06% CI, 3.3% to ∞; intention-totreat absolute risk difference, 12%; 97.06% CI, 1.7% to ∞) [28]. Adverse effects included a higher frequency of (usually nonlimiting) gastrointestinal symptoms with pristinamycin.…”
Section: Prospective Studiesmentioning
confidence: 95%
“…The writing group was unable to define the best treatment for cellulitis. However, the reviewers concluded that the limited evidence of three trials [28][29][30] suggested macrolide and streptogramin antibiotics are slightly better than penicillins for reducing symptoms at the end of antibiotic treatment for cellulitis.…”
Section: Evidence Summarymentioning
confidence: 99%